Data-Based Planning Workshop In Education Quality Assurance In Primary Schools Pamulihan District, Sumedang Regency - Sulastini, Rita; Agustini, Tita; Stefanie, Sylviana; Ruyatus, Selvia; Irnawati, Riska; Sopandi, Uus (PT. Riset Press International, 2025)
The Data-Based Planning Workshop in Education Quality Assurance in Elementary Schools Pamulihan District, Sumedang Regency aims to increase the understanding and skills of educators in planning educational policies and programs based on valid and relevant data. Through this workshop, participants are expected to be able to identify, collect and analyze data to support more effective decision making in improving the quality of education in elementary schools. The main focus of this workshop is to educate participants about the importance of using data in educational planning, as well as how to analyze and implement data to achieve better educational goals. Apart from that, this workshop also highlighted the importance of monitoring and evaluation in ensuring the sustainability of data-based planning. It is hoped that by implementing this concept, elementary schools can achieve more measurable and sustainable improvements in the quality of education.